``A COMPARATIVE STUDY ON PHYSIOCHEMICAL AND NUTRITIVE CONSTITUENTS OF MANIHOT ESCULENTA CRANZ AND IPOMOEA BATATAS - S.ANBUSELVI; T.BALAMURUGAN (International Journal of Pharma and Bio Sciences, 2013)
Human beings consumed starch in the form of cereals and tubers which provides 70-80% of calories to our body. Sweet potato plays a significant role in tribal Indian diet. It contains β-carotene and anthocyanin(antioxidant) rich. Recently it has been found out that sweet potato can control blood sugar levels and insulin resistance. The World Health Food Organization has labeled it as anti-diabetic food .Studies estimated that a daily intake of 100g of orange fleshed sweet potato prevent vitamin A deficiency in children and lactating mothers. Cassava contain 60-70% of starch in tubers and leaves. This Cassava tuber is used as staple food in India. It also contains high amount of protein present leaves (70%) for animal feed production. Cassava pulp and waste serve as a raw material for starch and monosodium glutamate production. It is also used as aubstrate for production of single cell protein and ethanol. Cassava pulp contains the maximum amount of non reducing sugar (6.6mg). Vitamin C was highly observed in leaves (300mg and waste (360mg). The proximate moisture, fat,proteins,crude fibre,ash and carbohydrates were determined in sweet potato and cassva samples